2021
DOI: 10.3390/jpm11070614
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of IgG Associates with Hypertension and Type 2 Diabetes Mellitus Comorbidity in the Chinese Muslim Ethnic Minorities and the Han Chinese

Abstract: Objectives: Hypertension and type 2 diabetes mellitus comorbidity (HDC) is common, which confers a higher risk of cardiovascular disease than the presence of either condition alone. Describing the underlying glycomic changes of immunoglobulin G (IgG) that predispose individuals to HDC may help develop novel protective immune-targeted and anti-inflammatory therapies. Therefore, we investigated glycosylation changes of IgG associated with HDC. Methods: The IgG N-glycan profiles of 883 plasma samples from the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Hypertension and diabetes are risk factors for the development of severe cardiovascular disease and are prevalent comorbidities [1][2][3][4][5][6][7][8][9][10][11]. The causal relationship between hypertension and diabetes is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension and diabetes are risk factors for the development of severe cardiovascular disease and are prevalent comorbidities [1][2][3][4][5][6][7][8][9][10][11]. The causal relationship between hypertension and diabetes is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The phenotype of glycans in healthy individuals is stable but can dramatically change under pathological conditions, such as inflammation and hypertension. 9,10 IgG, the most abundant glycoprotein in human biofluids and the main effector of the humoral immune system, is involved in inflammatory pathways and regulates systemic inflammatory homeostasis at multiple levels, primarily through its N-glycans. [11][12][13][14] The anti-and proinflammatory activities of IgG can be completely altered by its N-glycans.…”
mentioning
confidence: 99%
“…Twenty-seven N-glycan traits from IgG subclasses were associated with T2D in the Uyghur population [ 43 ]. In addition, a study of Chinese Muslim ethnicity and the Han population reported associations of IgG-glycans with hypertension and type 2 diabetes mellitus comorbidity [ 45 ]. A study of European samples developed a score based on significant IgG-GPs, which was associated with higher diabetes risk and was robust against confounder and clinical biomarkers [ 46 ].…”
Section: Discussionmentioning
confidence: 99%